A guideline for the outpatient management of glycaemic control in people with cancer. Issue 1 (16th July 2021) - Joharatnam‐Hogan, Nalinie; Chambers, Pinkie; Dhatariya, Ketan; Board, Ruth; ,
Abstract: Individuals with cancer are at increased risk of developing new‐onset diabetes mellitus and hyperglycaemia, and an estimated 20% of people with cancer already have an underlying diagnosis of diabetes mellitus. People with both cancer and diabetes may have an increased risk of toxicities, hospital admissions and morbidity, with hyperglycaemia potentially attenuating the efficacy of chemotherapy often secondary to dose reductions and early cessation. Numerous studies have demonstrated that hyperglycaemia is prognostic of worse overall survival and risk of cancer recurrence. These guidelines aim to provide the oncology/haemato‐oncology and diabetes multidisciplinary teams with the tools to manage people with diabetes commencing anti‐cancer/glucocorticoid therapy, as well as identifying individuals without a known diagnosis of diabetes who are at risk of developing hyperglycaemia and new‐onset diabetes.